Risk factors for hospital readmission of multidrug—resistant tuberculosis: evidence of longitudinal follow-up data in Ningbo, China - Huang, Jinying; Sang, Guoxin; Bi, Jianda; Che, Yang; Lin, Yi (Frontiers in Public Health, 2025)
ObjectivesMulti-drug-resistant tuberculosis (MDR-TB) continues to be a public health threat. Patients with MDR-TB commonly have a higher recurrence rate of hospital visits. However, previous studies have mainly focused on the time to the first event, while ignoring subsequent events. The objective of this study is to estimate the risk factors for the incidence of rehospitalization in MDR-TB patients.MethodsA retrospective longitudinal study was conducted on the MDR-TB patients who were consecutively enrolled from January 2015 to December 2021 in Ningbo, China. We fitted a multivariable Cox proportional hazard for time to first-event analysis, and extension of standard Cox model to consider multiple events.ResultsThe study included 337 patients, with a total of 1,255 hospitalization records analyzed and a median follow-up period of 46 months. Younger age (HR = 0.34, 95% CI: 0.20–0.57) and residing in urban areas (HR = 0.55, 95% CI: 0.37–0.83) were identified as protective factors against hospital readmission of MDR-TB patients. In contrast, outdoor service workers (HR = 1.51, 95% CI: 1.01–2.26) and migrants (HR = 1.79, 95% CI: 1.07–2.98) were associated with an increased risk of against hospital readmissions of MDR-TB patients. Furthermore, the extended Cox model revealed that both migrant status and the use of Group B medications significantly elevated the risk of hospital readmission of MDR-TB patients.ConclusionMDR-TB remains a heavy public health issue, especially those with the independent risk factors of living in the rural areas and migrants. Social health protection schemes and government financing are essential for ensuring early diagnosis and appropriate treatment of MDR-TB.